UNDERSTANDING THE CONCEPTS OF "TERMINOSYSTEM," "TERMINOLOGY," AND "TERMINOFIELD" - Ayaqulov Nurbek Abdug‘appor o‘g‘li (Journals Park Publishing, 2024)
The article focuses on defining the functional sphere of terms in modern linguistic science, specifically "terminology," "terminosystem," and "terminofield." The relevance of the research lies in the concurrent use of these three terms to describe a systematically organized set of terms within a specific knowledge domain. To determine whether these terms are synonyms or represent different concepts, their definitions are analyzed. The article also reviews the perspectives of prominent linguists on the distinctions between "terminology," "terminosystem," and "terminofield."
Keywords: special vocabulary; term; terminology; terminosystem; terminofield.